Actividad inhibitoria de extractos de Conyza bonariensis (L.) Cronquist y Acanthospermum australe (Loefl.) Kuntze frente a hongos y bacterias causantes de infecciones de piel - Mussin, Javier Esteban (2020)
Indigenous peoples are usually in close contact with nature and have a deep knowledge of the medicinal properties of plants. This knowledge has been practiced, documented and transmitted through generations, and allowed the pharmaceutical industry to develop a large number of drugs. For this, the medicinal properties of plants must undergo a process of scientific validation in terms of efficacy, safety and quality. These three concepts govern the current therapeutic of the 21st century inherent in any conventional drug and it allows medicinal plants to intervene in the development and advancement of modern medicine, serving as a starting point for the development of new drugs.\nCertain plants are used by the indigenous of Argentine northeast (NEA) for the treatment of various diseases. Among them, the use of "tapekué", vulgar name of Acanthospermum australe (Loefl.) Kuntze and "carnicera", vulgar name of Conyza bonariensis (L.) Cronquist, for the cure of skin infections, disinfection of wounds and ulcers, among other dermal conditions.\nSkin and soft tissue infections (IPPB) are a common reason for consultation in primary health care centers. They are clinical entities of variable presentation, etiology and severity that involve a microbial invasion of the skin layers and soft tissues, ranging from mild infections to life-threatening infections. The most common bacteria involved in IPPB are Streptococcus pyogenes, Pseudomonas aeruginosa and Staphylococcus aureus, while superficial fungal infections are mainly caused by Candida, Malassezia and dermatophyte species.\nMost of the inhabitants of the NEA live in an economically unfavorable context in terms of their possibilities to access drugs. Before this barrier, they resort to the knowledge of traditional medicine for the treatment and care of their health.\nThis work aimed to: obtain and characterize the aqueous extract, ethanolic extract and essential oil of tapekué and carnicera leaves of the NEA; determine whether the\nextracts and essential oils were not cytotoxic at the concentrations needed to inhibit microbial growth; evaluate in vitro inhibitory activity against fungi and bacteria causing IPPB, and determine if the interaction between extract-extract and extract-drug (drug of clinical use) was synergistic.\nThe characterization was carried out by: determining the content of flavonoids and total phenols of the extracts by spectrophotometric methods; determination of the chemical composition of essential oils by gas chromatography coupled to mass spectrometry; and evaluation of the antioxidant activity of extracts and essential oils based on the iron reducing capacity and DPPH radical scavenging capacity.\nToxicity was assessed against peripheral blood mononuclear cells. In vitro inhibitory activity was evaluated by determining the CIM according to the CLSI reference documents, with modifications. And the effect of the interaction between antimicrobial agents was evaluated by the chessboard method.\nThe aqueous and ethanolic extracts of both plants showed the presence of phenolic compounds, the content of phenols and flavonoids being significantly higher in the ethanolic extracts. On the other hand, the main components of the essential oil of leaves of C. bonariensis were limonene, spatulenol and ?-curcumene. While the main components of the essential oil of leaves of A. australe were germacrene A, ?-cadineno and trans-cariofileno. The evaluation of the antioxidant activity showed that the aqueous and ethanol extracts of both plants had significantly higher values of antioxidant activity compared to their respective essential oils.\nThe cytotoxicity test showed that extracts and essential oils are not toxic at the concentrations tested to inhibit microbial growth.\nAccording to the established criteria, the aqueous and ethanol extracts of both plants were inactive against the microorganisms tested. On the contrary, the essential oil of tapekué showed a strong activity against Epidermophyton floccosum and Microsporum canis; moderate activity against Malassezia globosa; low activity against Microsporum gypseum and Trichophyton tonsurans; and inactive against the other microorganisms\ntested. On the other hand, carnicera essential oil showed a strong activity against all dermatophytes and M. globosa; low activity against Malassezia furfur; and inactive against other microorganisms.\nAccording to the chessboard method, the only combination that presented a synergistic effect against Malassezia was the combination carnicera essential oil with tapekué essential oil.\nThe combinations between both essential oils and each essential oil with ketoconazole showed synergistic effects against M. canis, M. gypseum, E. floccosum and T. tonsurans. The most of the combinations with terbinafine showed effects of no interaction, except with carnicera essential oil against M. canis and M. gypseum, which presented a synergistic effect.\nThe results obtained provide the scientific evidence that supports the ancestral use of tapekué and carnicera leaves for the treatment of dermatophytosis and pityriasis versicolor, in addition to justifying the traditional use of combinations of medicinal plants.